Delusional Misidentification Syndrome (DMS) - An unidentified entity of DSM - Vidhi Patel; Sandeep Shah; Lakhan Kataria (Journal of Integrated Health Sciences)
Delusional misidentification syndromes (DMS), which includes the Capgras, Fregoli, Inter metamorphosis and Syndrome of Subjective doubles gain curiosity due to the bizarreness in their symptomatology. However they are diagnosed as some form of Schizophrenia and related psychosis and treated accordingly. An issue that remains unresolved is whether DMS (either in its pure form or as embedded symptoms of other diagnoses) can be accommodated in the present Diagnostic and Statistical Manual of Mental Disorders, (DSM-IV TR). As we await the DSM – V, it is still not clear as where do we diagnose patients with monothematic bizarre delusions due to lack of proper guidelines in DSM IV TR. Here we present two cases with Capgras Delusions and express our concern regarding the short comings of current Diagnostic system